High resolution muon computed tomography at neutrino beam facilities. (24th February 2016) - Suerfu, B.; Tully, C.G.
Abstract: X-ray computed tomography (CT) has an indispensable role in constructing 3D images of objects made from light materials. However, limited by absorption coefficients, X-rays cannot deeply penetrate materials such as copper and lead. Here we show via simulation that muon beams can provide high resolution tomographic images of dense objects and of structures within the interior of dense objects. The effects of resolution broadening from multiple scattering diminish with increasing muon momentum. As the momentum of the muon increases, the contrast of the image goes down and therefore requires higher resolution in the muon spectrometer to resolve the image. The variance of the measured muon momentum reaches a minimum and then increases with increasing muon momentum. The impact of the increase in variance is to require a higher integrated muon flux to reduce fluctuations. The flux requirements and level of contrast needed for high resolution muon computed tomography are well matched to the muons produced in the pion decay pipe at a neutrino beam facility and what can be achieved for momentum resolution in a muon spectrometer. Such an imaging system can be applied in archaeology, art history, engineering, material identification and whenever there is a need to image inside a transportable object constructed of dense materials.